Pulmonary artery aneurysm: computed tomography (CT) imaging findings and diagnosis - Bu, C.; Zhang, M.; Sun, Q.; Zhang, H.; Luo, J.; Liu, Q.; Sun, Zhonghua; Li, Y. (AME Publishing Company, 2024)
Pulmonary artery aneurysm (PAA) is a rare pulmonary vascular disease with nonspecific symptoms and various etiologies. As the disease progresses, in addition to the dilation of the pulmonary arteries, it may be accompanied by remodeling of the cardiac structure and changes in the morphology of the aorta. Recognizing the cause of PAA is therefore a clinically challenging task. In this review article, we provide an overview of various causes of PAA with the support of corresponding imaging findings on computed tomography pulmonary angiography (CTPA) examination. Firstly, from the perspective of hemodynamics, a logical diagnosis is provided according to whether the main pulmonary artery (MPA) is dilated, and whether the PA is dilated locally or diffusely. Secondly, for the imaging examination of vascular wall lesions, due to the limitations of ultrasound examination and interventional procedures, the irreplaceability of dual-phase CTPA examination in disease assessment is especially emphasized. Finally, for highly suspected disorders, it is necessary to comprehensively check with the patient whether there is a family history or past medical history. For patients with PAA, especially those with Marfan syndrome (MFS) or arteritis, adequate preoperative imaging evaluation, regular postoperative radiographic follow-up, and concurrent treatment of the underlying disease (if necessary) are crucial, which are related to the prognosis and long-term quality of life of such patients. Despite the nonspecific features of PAA presentation, a thorough examination of the patient’s clinical history and imaging characteristics will play an important role in diagnosing PAA and planning patient management str